MENINGKATKAN KEMAMPUAN PROMOSI DAN PEMASARAN UMKM LENGKONG KARYA - Azzahra, Annisaa; Muzaki, Afriza Ikhsan; Nur Fadhilah, Kayla Zahrah; Alfarizy, Mochammad Ferdy; Ningrum, Novita Widya; Sucipto, Rakhmat Hadi (Smart Education, 2025)
Abstract: Micro, small, and medium enterprises (MSMEs) play an important role in encouraging regional economic growth, including those in the Lengkong Karya Village area, North Serpong District, South Tangerang City. However, MSME actors in this region still face various obstacles, especially in the marketing aspect. Therefore, support from outside parties, including universities, is to improve their abilities. With this fact, Bina Sarana Informatics University (UBSI), especially through the BSI Explore community service program, is here to help develop MSMEs in the Lengkong Karya area. The team made socialization activities, especially about more optimal sales and promotion techniques, assistance in making Business Identification Numbers (NIB), and making business logo designs to increase buyer attraction. Methods to make this activity a success include interactive training, direct mentoring, creative workshops, and outcome mapping-based evaluations. The results of the activity show that there is an increase in the understanding and skills of MSME actors in utilizing digital technology for marketing. As a result, there has been an increase in turnover and a wider market reach. Keyword: lengkong karya; MSMEs; regional economy Abstrak: Usaha mikro, kecil, dan menengah (UMKM) berperan peran penting mendorong pertumbuhan ekonomi daerah, termasuk yang berada di wilayah Kelurahan Lengkong Karya, Kecamatan Serpong Utara, Kota Tangerang Selatan. Meski demikian, pelaku UMKM di wilayah ini masih menghadapi berbagai kendala, terutama dalam aspek pemasaran. Oleh karena itu, dukungan dari pihak luar, termasuk perguruan tinggi, demi meningkatkan kemampuan mereka. Dengan fakta tersebut, Universitas Bina Sarana Informatika (UBSI) terutama melalui program pengabdian masyarakat BSI Explore hadir untuk membantu mengembangkan UMKM di wilayah Lengkong Karya. Tim membuat kegiatan sosialisasi terutama tentang teknik penjualan dan promosi yang lebih optimal, pendampingan pembuatan Nomor Induk Berusaha (NIB), serta pembuatan desain logo usaha guna meningkatkan daya tarik pembeli. Metode untuk menyukseskan kegiatan ini di antaranya adalah dengan pelatihan interaktif, pendampingan langsung, workshop kreatif, dan evaluasi berbasis outcome mapping. Hasil kegiatan menunjukkan, ada peningkatan pemahaman dan keterampilan pelaku UMKM dalam memanfaatkan teknologi digital untuk pemasaran. Imbasnya, terjadi peningkatan omzet serta jangkauan pasar yang lebih luas. Kata kunci: ekonomi daerah; lengkong karya; umkm